Expressão de canais de cálcio em colangiócitos na doença hepática alcoólica - Kemper Nunes dos Santos (2021)
Alcohol is the most widely used addictive substance by man and its excessive consumption is the third leading preventable cause of death in the world, with more than 3 million deaths (5.3%) in 2016. Alcoholic liver disease (ALD) is among the main causatous factors of morbidity and mortality, responsible for 47.9% of cases of liver failure attributed to cirrhosis. Studies have suggested that during ALD cholestatic liver injury may occur, in which this manifestation is associated with an unfavorable prognosis of this disease. Chronic alcohol induction can cause impairment in the levels of ITPR3 and decreased activity of calcium channels in cholangiocytes. We aimed to determine the evidence in the frequency of ITPR3 expression in cholangiocytes in cases of cirrhosis caused by ALD and the correlation between simple nucleotide polymorphisms (SNPs) to the susceptibility of ALD. Immunohistochemistry (IHC) and molecular biology analyses were performed using the polymerase chain reaction (PCR) technique, in 49 liver biopsy samples from cases diagnosed with cirrhosis caused by ALD, compared to 18 cases of hepatitis C virus (HCV) infection and 21 liver biopsies from liver transplant donors. The results showed genotypic variations in the promoter region of the nuclear Factor, Erythroid 2 Like 2 gene (NFE2L2), for the -214A allele (p = 0.0136), both in homozygosis -214A/A and heterozygosis -214A/G (p = 0.0428), were significantly associated as a probable genetic biomarker at a higher risk in ALD, since they were significant at a lower level of expression of Nrf2 transcription factor in cholangiocytes and to a higher inflammatory activity during ALD. In conclusion that during chronic alcohol induction in ALD, there is a compromise of ITPR3 expression levels in cholangiocytes and that genetic factors associated with SNP rs35652124 (-214A), NFE2L2 gene, is associated with a higher risk and susceptibility to progression in ALD.